2016
DOI: 10.1371/journal.pone.0157220
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3DE Inhibits LINE-1 Retrotransposition by Interacting with ORF1p and Influencing LINE Reverse Transcriptase Activity

Abstract: Human long interspersed elements 1 (LINE-1 or L1) is the only autonomous non-LTR retroelement in humans and has been associated with genome instability, inherited genetic diseases, and the development of cancer. Certain human APOBEC3 family proteins are known to have LINE-1 restriction activity. The mechanisms by which APOBEC3 affects LINE-1 retrotransposition are not all well characterized; here, we confirm that both A3B and A3DE have a strong ability to inhibit LINE-1 retrotransposition. A3DE interacts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 51 publications
2
36
0
2
Order By: Relevance
“…A3DE is expressed in hESC, associates with ORF1p protein in an RNAdependent manner and this interaction causes a strong inhibition of the ORF2p RT activity (Liang et al 2016). The authors showed also a weak RNA-dependent interaction between A3B and ORF1p, but failed to observe any effect of this enzyme on ORF2p activity, thus suggesting a different inhibitory mechanism.…”
Section: Inhibition Of Line-1 and Alu Retrotransposition Mediated By mentioning
confidence: 95%
See 3 more Smart Citations
“…A3DE is expressed in hESC, associates with ORF1p protein in an RNAdependent manner and this interaction causes a strong inhibition of the ORF2p RT activity (Liang et al 2016). The authors showed also a weak RNA-dependent interaction between A3B and ORF1p, but failed to observe any effect of this enzyme on ORF2p activity, thus suggesting a different inhibitory mechanism.…”
Section: Inhibition Of Line-1 and Alu Retrotransposition Mediated By mentioning
confidence: 95%
“…Several members of the AID/APOBEC family (AID, A1, A3A, A3B, A3C, A3DE, A3F and A3H) were shown to inhibit both LINE-1 and Alu retrotransposition (Pizarro and Cristofari 2016;Bogerd et al 2006;Muckenfuss et al 2006;Chen et al 2006;Stenglein and Harris 2006;Kinomoto et al 2007;Niewiadomska et al 2007;Richardson et al 2014;Koyama et al 2013;Horn et al 2014;Liang et al 2016;Feng et al 2017;Ikeda et al 2011). The majority of these experiments were carried out in cell cultures and the inhibition was found to be mainly mediated by editing-independent mechanisms (Pizarro and Cristofari 2016).…”
Section: Inhibition Of Line-1 and Alu Retrotransposition Mediated By mentioning
confidence: 99%
See 2 more Smart Citations
“…First, since A3 enzymes bind RNA with high affinity, it was thought that the A3 enzymes would act as a roadblock to reverse transcription. Similarly, A3s could bind the LINE-1 RNA in the cytoplasm and cause it to accumulate in cytoplasmic RNA processing bodies (P-bodies), preventing nuclear import [167,168]. DNA sequencing of integrated LINE-1 genomes had little evidence of cytosine deamination, which supports these mechanisms mediated by RNA binding.…”
Section: Restriction Of Endogenous Retroelements By Apobec3mentioning
confidence: 92%